2020
DOI: 10.3390/ijms21228591
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA, the Key for Translation

Abstract: It was thought until the 1990s that the eukaryotic translation machinery was unable to translate a circular RNA. However internal ribosome entry sites (IRESs) and m6A-induced ribosome engagement sites (MIRESs) were discovered, promoting 5′ end-independent translation initiation. Today a new family of so-called “noncoding” circular RNAs (circRNAs) has emerged, revealing the pivotal role of 5′ end-independent translation. CircRNAs have a strong impact on translational control via their sponge function, and form … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 101 publications
0
50
0
Order By: Relevance
“…Many of the genes involved in angiogenesis or cardioprotection tested here have not been described for containing an IRES in their mRNAs. We can make the hypothesis that these mRNA families either contain IRESs that have not been identified yet, or are translated by another cap-independent mechanism such as m6A-induced ribosome engagement sites (MIRES) (Prats et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the genes involved in angiogenesis or cardioprotection tested here have not been described for containing an IRES in their mRNAs. We can make the hypothesis that these mRNA families either contain IRESs that have not been identified yet, or are translated by another cap-independent mechanism such as m6A-induced ribosome engagement sites (MIRES) (Prats et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is considered conventionally that circRNAs are noncoding RNAs, but some circRNAs have been inspected to have protein‐encoding capability through the following ways: ribosome entry site (IRES) (Prats et al, 2020; Yang et al, 2018), rolling circle amplification (RCA) (Abe et al, 2015), untranslated regions (UTR) (Pamudurti et al, 2017), and N6‐methyladenosine (m 6 A) (Yang et al, 2017)—driven translation mechanisms. For the IRES‐driven translation mechanism, IRES are located in the upstream frame of some circRNA start codons where they induce circRNA translation (Prats et al, 2020). Yang et al (2018) observed that IRES induced circ‐FBXW7 to encode a 21‐kDa protein, FBXW7‐185aa.…”
Section: Biogenesismentioning
confidence: 99%
“…However, more recently, circRNAs have been found to encode peptides, where an Internal Ribosome Entry site and N 6 -methyladenosines mediated cap-independent translation initiation were suggested as potential mechanisms involved in the translation of circRNAs. Detailed mechanisms of circRNA translation are reviewed elsewhere (28)(29)(30). Legnini et al (31) provided an example of translatable circRNAs in eukaryotes, suggesting that circ-zinc finger protein 609 (circZNF609) was translated into protein in a splicing-dependent and cap-independent manner, and this was shown to be involved in regulating myogenesis.…”
Section: Circrna Functionmentioning
confidence: 99%